Structures associated with feeding in Mastacembelus armatus (Lacepede, 1800) from Kaigaon Toka (M.S.) - Anand, Sunil; Gedam, Ajit; Sonawane, Smita (Journal of Experimental Sciences, 2013)
The structures associated with feeding of Mastacembelus armatus shows interesting modifications reflecting carnivorous mode of feeding habit with several morphological characters such as, mouth equipped with fine but firm jaws, upper jaw longer projecting over the lower jaw, buccal cavity is narrow, pharynx is wide, spacious and dorso-ventrally compressed, Teeth are sharp, tiny, robust, subequal, inclined inwards, villiform organised in patches, gill rakers are absent.